'Hogwash': Addiction Policy Foundation on opioid bill reports. Issue 35 (14th September 2018) - Knopf, Alison
Abstract : Last week, as the Senate headed toward a vote on the opioid package, the Addiction Policy Forum was weathering an attack in the form of almost identical stories in Congressional Quarterly and Politico that said Democrats were opposed to a provision in the bill that favors the advocacy organization. According to both reports, which came out Sept. 5, Democrats objected to the language that would give $10 million a year for five years to an advocacy organization, language that would apply only to the Addiction Policy Forum. The unnamed Democrat staffers, according to the stories, pinned their criticism on the fact that the Addiction Policy Forum receives pharmaceutical funding, something the organization itself announced last December (see ADAW, Jan. 8) but created a minor ruckus after protesters from Minnesota accused the group of a conflict of interest in a story published in The New York Times (see ADAW, Feb. 19, 2018).